2006
DOI: 10.1152/ajpregu.00616.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of progranulin expression in myeloid cells

Abstract: Progranulin (pgrn; granulin-epithelin precursor, PC-cell-derived growth factor, or acrogranin) is a multifunctional secreted glycoprotein implicated in tumorigenesis, development, inflammation, and repair. It is highly expressed in macrophage and monocyte-derived dendritic cells. Here we investigate its regulation in myeloid cells. All-trans retinoic acid (ATRA) increased pgrn mRNA levels in myelomonocytic cells (CD34 ϩ progenitors; monoblastic U-937; monocytic THP-1; progranulocytic HL-60; macrophage RAW 264.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 57 publications
3
40
0
Order By: Relevance
“…It is reported to be involved in cancer progression 8) , development 12) , wound healing 13) , and myeloid cell proliferation 14) , whereas mutation of progranulin causes frontotemporal dementia 15,16) . In the present study, we demonstrated that the macrophage-secreted factor was approximately 130 kDa, while the purified protein identified as progranulin was 80 kDa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported to be involved in cancer progression 8) , development 12) , wound healing 13) , and myeloid cell proliferation 14) , whereas mutation of progranulin causes frontotemporal dementia 15,16) . In the present study, we demonstrated that the macrophage-secreted factor was approximately 130 kDa, while the purified protein identified as progranulin was 80 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…The 130-kDa HDL binding protein might be a homodimer or heteromer that includes progranulin, which is known to be glycosylated and to have disulfide bonds 11) . Ong and colleagues 14) used myeloid cell lines and reported the overexpression of progranulin in macrophages and monocyte-derived dendritic cells, and that the level of expression was dependent on cell differentiation. Our results also demonstrated that the differentiation of human monocyte-derived macrophages was associated with increased expression levels of progranulin and that progranulin expression was regulated in an autocrine fashion in human monocytederived macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Reference annexin 1 (Parente and Solito, 2004) annexin 2, annexin II type 1 (Abbas et al, 2005) annexin 5 (Munoz et al, 2007) B fibrinopeptide (Mosesson et al, 2001) calpactin I (annexin II) light chain p11 subunit (Laumonnier et al, 2006) complement component 1 q subcomponent binding protein (Abbas et al, 2005) elastase 2 (Horwitz et al, 2007) fibrinogen alpha (Ugarova and Yakubenko, 2001) fibrinogen gamma (Ugarova and Yakubenko, 2001) gelatinase B, matrixmetalloproteinase 9 (Abbas et al, 2005) granulin (Ong et al, 2006) integrin alpha V subunit (Schoeler et al, 2003) interferon regulatory factor 2 binding protein 2 (Childs and Goodbourn, 2003) lymphocyte cytosolic protein 1 (Abbas et al, 2005) manganese superoxide dismutase (Abbas et al, 2005) moesin (Abbas et al, 2005) myeloperoxidase, peroxidase 2 (Rutgers et al, 2003) phosphatidylserine decarboxylase (Abbas et al, 2005) prohibitin (Theiss et al, 2007) putative cathepsin L (Abbas et al, 2005) slingshot-related protein (Abbas et al, 2005) transaldolase 1 (Abbas et al, 2005) transferrin, lactotransferrin (Weinberg, 2007) vimentin (VIM1, VIM4) (Benes et al, 2006) Protein Name SC Types References actin beta MSC, NSC (Baharvand et al, 2007) actin gamma MSC, NSC (Baharvand et al, 2007) aldolase A ESC, MSC (Baharvand et al, 2007) annexin 1 MSC, NSC (Baharvand et al, 2007) annexin 2, annexin II type 1 MSC, NSC (Baharvand et al, 2007) annexin 5 MSC, NSC (Baharvand et al, 2007) annexin 7 MSC (Kim et al, 2006) ATP-dependent chromatin remodeling DEXH-box protein NSC (Matsumoto et al, 2006) ferritin ADSC (Zvonic et al, 2007) glutathione-S-transferase ADSC …”
Section: Protein Namementioning
confidence: 99%
“…At a cellular level, progranulin is a secreted growth factor expressed in epithelial cells, hematopoetic cells, adipocytes, immune cells, and certain types of neurons (3)(4)(5)(6)(7). Mutations in the GRN gene encoding progranulin are a leading cause of frontotemporal dementia (8,9).…”
mentioning
confidence: 99%